2001
DOI: 10.1002/path.1013
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte macrophage‐colony stimulating factor (GM‐CSF) recruits immune cells to the pancreas and delays STZ‐induced diabetes

Abstract: Granulocyte macrophage-colony stimulating factor (GM-CSF) is one of the most widely used growth factors for enhancing immune responses and is known to recruit and activate antigen-presenting cells (APCs). This study hypothesized that overexpression of this cytokine within the pancreatic beta-cells would recruit, expand, and activate APCs. The question was whether this would lead to tolerance or autoimmunity to pancreatic antigens. This possibility was tested by preparing transgenic mice (ins-GM-CSF) whose isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Our results demonstrate that GM-CSF expressed within the g -cells of the islets of Langerhans enhanced disease incidence in male NOD mice due to an increase in the availability of islet antigen. Recent studies have shown diverse functions of GM-CSF in the immune system [20,21,27,[32][33][34]. Our results suggest that in ins-GM-CSF mice, this height-ened response is mediated by increased numbers of APC infiltrating the pancreas as well as enhanced expression of B7-1 in CD11b + cells.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our results demonstrate that GM-CSF expressed within the g -cells of the islets of Langerhans enhanced disease incidence in male NOD mice due to an increase in the availability of islet antigen. Recent studies have shown diverse functions of GM-CSF in the immune system [20,21,27,[32][33][34]. Our results suggest that in ins-GM-CSF mice, this height-ened response is mediated by increased numbers of APC infiltrating the pancreas as well as enhanced expression of B7-1 in CD11b + cells.…”
Section: Discussionmentioning
confidence: 57%
“…To prepare ins-GM-CSF×NOD mice, the approximately 425-bp mouse GM-CSF cDNA was isolated and cloned into a vector containing the human insulin promoter and hepatitis B 3'-untranslated sequence as previously described [21].…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…19 Because hepatosplenomegaly is frequently observed in flaviviral infections, 43,44 and up-regulated GM-CSF and IL-1␤ serum levels correlate with disease severity, 11 GM-M is probably the dominant macrophage subset during flaviviral infection. This argument is supported by the observation that DV-infected M-M did not produce IL-1␤; thus, GM-M seems to play a more important role than M-M in the pathogenesis of DV infection.…”
Section: Dv-induced Inflammasome Activation Is Via Clec5amentioning
confidence: 99%
“…This observation suggests that macrophage differentiation during inflammatory reactions is under the influence of GM-CSF, which can cause massive increase of macrophage population in spleen and induce splenomegaly. 19 Based on these findings, Hamilton 17 suggested that constant level of M-CSF is crucial to maintain M population in a homeostatic and resting condition (denoted as resting M ), whereas the local and temporal increase of GM-CSF during inflammation polarizes M to an inflammatory stage (denoted as inflammatory macrophage). Recently, an epidemiologic study demonstrated that elevated GM-CSF in the plasma of DV patients correlates with the severity of DF/DHF, 11 suggesting that DV infection may switch macrophages from resting to inflammatory status in DV patients and affect the gravity of clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%